International share portfolio diversification: Possible benefits for South African investors - N. Bhana (South African Journal of Business Management, 1986)
The De Kock Commission has recommended that exchange control regulations be relaxed so that South African investors may acquire foreign securities. The possible gains accruing to South African investors from international share portfolios representing 18 different countries for the period 1969-1983 were investigated. The inclusion of foreign securities results in superior portfolio returns when compared with returns derived from exclusive investment in South African securities. Furthermore, the South African investor accomplishes significant risk reduction when several foreign countries are included in international portfolios. The returns on South African goldmining shares are negatively correlated with most foreign shares. Therefore, goldmining shares feature prominently in optimal portfolios available to South African investors. By contrast local industrial shares are not included in any of the efficient frontiers. Although the currency factor is important, it was not a major element in the performance and risk components of international portfolios during the study period. The currency factor also constitutes a small percentage of the total risk of an unweighted portfolio representing the 18 selected countries. The importance of the currency factor is minimized due to low and possibly even negative correlations between share prices and exchange rate movements in the different countries.
Keywords: 650